An Atlas of the Quantitative Protein Expression of Anti-Epileptic-Drug Transporters, Metabolizing Enzymes and Tight Junctions at the Blood-Brain Barrier in Epileptic Patients - Risa Sato; Kotaro Ohmori; Mina Umetsu; Masaki Takao; Mitsutoshi Tano; Gerald Grant; Brenda Porter; Anthony Bet; Tetsuya Terasaki; Yasuo Uchida (MDPI AG, 2021)
The purpose of the present study was to quantitatively elucidate the levels of protein expression of anti-epileptic-drug (AED) transporters, metabolizing enzymes and tight junction molecules at the blood-brain barrier (BBB) in the focal site of epilepsy patients using accurate SWATH (sequential window acquisition of all theoretical fragment ion spectra) proteomics. Brain capillaries were isolated from focal sites in six epilepsy patients and five normal brains; tryptic digests were produced and subjected to SWATH analysis. MDR1 and BCRP were significantly downregulated in the epilepsy group compared to the normal group. Out of 16 AED-metabolizing enzymes detected, the protein expression levels of GSTP1, GSTO1, CYP2E1, ALDH1A1, ALDH6A1, ALDH7A1, ALDH9A1 and ADH5 were significantly 2.13-, 6.23-, 2.16-, 2.80-, 1.73-, 1.67-, 2.47- and 2.23-fold greater in the brain capillaries of epileptic patients than those of normal brains, respectively. The protein expression levels of Claudin-5, ZO-1, Catenin alpha-1, beta-1 and delta-1 were significantly lower, 1.97-, 2.51-, 2.44-, 1.90- and 1.63-fold, in the brain capillaries of epileptic patients compared to those of normal brains, respectively. Consistent with these observations, leakage of blood proteins was also observed. These results provide for a better understanding of the therapeutic effect of AEDs and molecular mechanisms of AED resistance in epileptic patients.